IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI MDTA USWAH AL-ISLAM - Fuad Hasan Harahap; Bardansyah; Azizah Hanum OK (Jurnal Binagogik, 2024)
The study of the search for MDTAs that have indeed implemented multicultural-based education either vaguely or not. Therefore, the background of the problem in the paper rests on not knowing whether the Islamic-based MDTA has implemented multicultural education, but in other descriptions there are MDTAs that have consciously and vaguely implemented multicultural education.